Knowledge about osteoarthritis: Development of the Hip and Knee Osteoarthritis Knowledge Scales and protocol for testing their measurement properties. Issue 2 (June 2021) - Darlow, Ben; Abbott, Haxby; Bennell, Kim; Briggs, Andrew M.; Brown, Melanie; Clark, Jane; Dean, Sarah; French, Simon; Hinman, Rana S.; Krägeloh, Chris; Metcalf, Ben; O'Brien, Daniel; et al.
Abstract: Objectives: 1) Develop unidimensional instruments to measure osteoarthritis (OA) knowledge among people with hip or knee OA, and 2) assess the structural validity, internal consistency, cross-cultural validity/measurement invariance, test-retest reliability, and measurement error of the Hip Osteoarthritis Knowledge Scale (HOAKS) and the Knee Osteoarthritis Knowledge Scale (KOAKS). Methods: Draft HOAKS and KOAKS were developed and refined following best-practice (COSMIN) guidelines with involvement of consumer research partners. Measurement properties of the HOAKS and KOAKS will be assessed through an online survey. The survey will include the novel HOAKS or KOAKS, the current short form of the Hip or Knee injury and Osteoarthritis Outcome Score (HOOS-12/KOOS-12), and items that gather demographic and OA characteristics and explore self-rated OA knowledge. People will be eligible to participate if aged 18 years and older, can communicate in English, and have either hip or knee OA as diagnosed by a health professional or by meeting diagnostic criteria. We aim to obtain 400 complete HOAKS or KOAKS responses and 100 complete HOAKS or KOAKS retest responses one week after initial completion. Rasch analysis will estimate structural validity, internal consistency and cross-cultural validity/measurement invariance. Assessment will include test-retest reliability (intraclass correlation coefficient) and absolute measurement error (standard error of measurement; smallest detectable change). Conclusion: This study will produce robust unidimensional instruments to measure hip and knee OA knowledge. We anticipate that the HOAKS and KOAKS scales will be useful in clinical and research settings to identify knowledge gaps or evaluate interventions designed to improve knowledge.